Attenuation control of pyrG expression in Bacillus subtilis is mediated by CTP-sensitive reiterative transcription - Meng, Qi (National Academy of Sciences, 2004)
In Bacillus subtilis and other Gram-positive bacteria, pyrimidine-mediated regulation of the pyrG gene, which encodes CTP synthetase, occurs through an attenuation mechanism involving an intrinsic transcription terminator in the pyrG leader region. Low intracellular levels of CTP prevent termination at the attenuator by a mechanism that requires the nontemplate strand sequence GGGC at the pyrG transcription initiation site (first G =+1) and the leader transcript sequence GCUCCC located at the 5′ end of the terminator RNA hairpin. In this study, we demonstrate that reiterative transcription adds G residues (up to at least 10) to the 5′ end of pyrG transcripts when B. subtilis cells are starved for pyrimidines but not when cells are grown with excess cytidine. Regulated repetitive addition of G residues, as well as pyrimidine-mediated pyrG regulation, requires the sequence GGGC or GGGT at the start of pyrG transcription. Mutational insertion of four extra G residues at the 5′ end of the pyrG transcript (i.e., 5′-GGGGGGGC) results in constitutive pyrG expression. We propose that the incorporation of extra G residues by reiterative transcription at the wild-type promoter occurs when normal transcription elongation is stalled at position +4 by low levels of the incoming substrate, CTP, during pyrimidine limitation. The poly(G) extensions on the 5′ ends of pyrG transcripts act to prevent transcription attenuation by base pairing with the sequence CUCCCUUUC located in the 5′ strand of the terminator hairpin. This control mechanism is likely to operate in other Gram-positive bacteria containing similar pyrG leader sequences.